Off-site impacts of wildfires on aquatic systems - Biomarker responses of the mosquitofish Gambusia holbrooki - Nunes, Bruno (2022)
The number of wildfires has markedly increased in Mediterranean Europe, including in Portugal. Wildfires are environmentally concerning, not only due to the loss of biodiversity and forest area, but also as a consequence of environmental contamination by specific compounds including metals and polycyclic aromatic compounds (PAHs). These contaminants, mostly bound to ashes, can reach downstream water bodies, namely through surface runoff, being ultimately dispersed by vast areas and contacting with aquatic biota. Being toxicologically noteworthy, the potential toxic outcomes of the input of such chemicals across the aquatic compartment must be characterized. In this context, the present study used a biomarker-based approach to find early-warning signals of toxicity triggered by the exposure of the mosquitofish, Gambusia holbrooki, to affected aqueous runoff and stream water samples collected from a forest burnt area. The chemical analysis revealed concerning levels of metals and polycyclic aromatic hydrocarbons in both runoff and stream water samples. Biological responses elicited by the collected samples showed the occurrence of pro-oxidative modifications, specifically driven by enzymatic forms involved in the metabolism of glutathione. Despite these effects, no further signs of involvement of metals and PAHs were elicited in terms of neurotoxicity. The overall set of data implicates chemicals resulting from wildfires in clear deleterious effects in exposed fish.